Faktor-Faktor yang Mempengaruhi Turnover Intention di PT. Daya Surya Sejahtera Ponorogo - Yuvi Safitri; Umi Farida; Fery Setiawan (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to identify the influence of job satisfaction, occupational health and safety (OHS), and work stress on turnover intention among employees of PT. Daya Surya Sejahtera Ponorogo. The phenomenon of high employee turnover rates is a significant issue that has the potential to hamper the smooth operation and stability of company productivity. Employees who intend to leave the company may indicate dissatisfaction with the work environment, workload, or lack of adequate job safety guarantees. Therefore, an in-depth study is needed to understand the factors that influence this intention. This study uses a quantitative approach with a survey method through the distribution of questionnaires to respondents. The sampling technique used a simple random sampling method with calculations using the Slovin formula, resulting in a sample size of 72 respondents from a total population of 250 employees. The collected data were analyzed using multiple linear regression methods with the help of SPSS version 25 software to test the influence of each independent variable on the dependent variable of turnover intention. The results of the analysis show that the three variables, namely job satisfaction, OHS, and work stress, simultaneously and partially have a significant influence on turnover intention. Low job satisfaction, perceptions of an unsafe work environment, and high levels of stress are the main triggers for employees' desire to leave the company. Therefore, companies are advised to improve job satisfaction through salary adjustments, career development opportunities, and comprehensive improvements to their OHS programs. Furthermore, employee stress management requires a systematic and sustainable approach to reduce employee turnover intentions.